A new fossil species Firkantus storozhenkoi Manukyan, sp. nov. (Hymenoptera: Ichneumonidae: Pimplinae) from the Eocene Baltic amber, with a key to Baltic amber Pimplinae - Manukyan, Andranik R.; Smirnova, Anna V.; Sinelschikova, Alexandra Yu. (Zootaxa, 2025)
A new species, Firkantus storozhenkoi Manukyan, sp. nov., is described from the late Eocene Baltic amber. A key to five fossil species of Pimplinae known from the Baltic amber is provided.